Acute Pain Management for a Tibial Plateau Fracture Shortly After a Buprenorphine XR Depot Injection: A Case Report. Issue 5 (28th September 2022) - Sivanathan, Lavarnan; Logan, Elizabeth; Popovski, Katherine; Goel, Akash; Hauck, Tanya; Ladha, Karim S.
Abstract : Acute pain management of patients on buprenorphine for opioid use disorder remains a challenge. The buprenorphine extended-release depot injection which lasts for 1 month and has a higher plasma concentration of buprenorphine compared to the sublingual formulation is increasingly being used in patients. Acute pain management of patients on buprenorphine depot remains a challenge because waiting for the washout of the medication is not feasible and discontinuation is challenging because it requires surgical excision. We describe here the pharmacokinetics of the buprenorphine depot formulation and the clinical implications of its long duration of action. A 39-year-old woman with a history of alcohol and opioid use disorder, on buprenorphine depot, was admitted to the hospital with a left tibial plateau fracture. Acute pain service managed her pain by utilizing a multimodal analgesia plan including femoral and popliteal nerve catheters, intravenous patient-controlled analgesia and oral opioid and nonopioid medications. The patient had a prolonged length of stay of 11 days but was successfully weaned off nerve catheters and intravenous medications and converted to an oral medication regiment such that she could be discharged from the acute care hospital.